La metodología en el proceso enseñanza del área de Matemática en los estudiantes del quinto grado de Educación Básica en la escuela Patronato Municipal de Amparo Social-Latacunga. - Changalombo Saquinga, Byron Rodrigo (2021)
The research report prepared focuses on the problems that exist in the teaching of Mathematics by teachers at the moment of demonstrating the achievement of learning in students. The objective of the research focuses on developing an activity guide through a methodological strategy to strengthen the teaching of Mathematics and develop critical and reflective thinking in a dynamic and effective way. To achieve the research a mixed approach was used that allowed the systematic integration of qualitative and quantitative methods in order to get, collect and analyze the information of the study phenomenon, a qualitative approach was applied at the moment the problem was detected and visualized and in the results when the proposal was validated ; the quantitative approach to the description of the data that served to diagnose the current situation of teachers in relation to the use of the Inverted Classroom methodological strategy, the acceptance of the proposal and its application when validated by specialists and users. The methods of analysis and synthesis were applied during the bibliographic review in educational theories and, particularly, when talking about methodological strategies in the teaching of Mathematics. It was feasible at getting bibliographic information from different research works and a modeling method was used to conform the system of procedures linked to the objectives and to elaborate the proposal because a change is required through the application of the Inverted Classroom as a methodological strategy in the teaching of Mathematics.